ANALISIS KINERJA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN KEPULAUAN MERANTI DALAM MENINGKATKANAN KUALITAS PELAYANAN PUBLIK - Dora, Rezkia Reisa (JISIP UNJA (Jurnal Ilmu Sosial Ilmu Politik Universitas Jambi), 2018)
This study discusses the Disdukcapil Performance of Meranti Islands District in Improving the Quality of Public Services. The type of research used in this study is qualitative descriptive. In this study, the subjects studied were Disdukcapil's performance in improving the quality of public services. The location of the study is the Population and Civil Registration Service of the Meranti Islands Regency. In this study using data collection techniques of observation, interviews, and documentation. Data analysis techniques used are interpretative data analysis. From the research conducted, the results of the research are based on several indicators, namely as follows: In terms of ethical ethics, employees still show an inappropriate attitude and have not fully fulfilled their attitude in excellent service. In terms of time there are still delays in the settlement. Another weakness is the lack of understanding of the quality management of services for employees in charge of serving. In terms of responsiveness it can be said that there are still deficiencies. In an effort to improve the quality of public services, the Merdukcapil District of Meranti Regency has not yet been fully realized.